THE INFLUENCE OF INFLATION AND POPULATION GROWTH ON WEST SULAWESI'S ECONOMIC GROWTH IN THE 2013-2018 PERIOD - Awal Nopriyanto Bahasoan; Fausiah; Aminah; Samsuardi Said (Jurnal Ekonomi, 2023)
Sustainable economic growth is the main goal for most countries in the world, including Indonesia. High economic growth can improve people's welfare, create new jobs, increase a country's competitiveness in the global market, and strengthen social and economic stability. This study aims to analyze the effect of inflation and population growth on economic growth in West Sulawesi in the 2013-2018 period . This study uses the Fixed Effect Model method with panel data. The data used in this study comes from the West Sulawesi Central Bureau of Statistics. The results of his research show that inflation and population growth have had a positive and significant effect on economic growth in West Sulawesi during the observed period, but it is necessary to control inflation and population growth appropriately in order to support sustainable economic growth